Pengembangan Media Pembelajaran Matematika Interaktif Menggunakan Powerpoint Ispring pada Materi Bilangan Rasional Kelas VII SMP Muhammadiyah 01 Medan - Widia Yanti Ujung; Asrul Asrul; Ammamiarihta Ammamiarihta (Educational Journal, 2026)
This study aims to develop an iSpring-based PowerPoint that is valid, practical, and effective in improving the mathematical problem-solving abilities of seventh-grade students at SMP Muhammadiyah 01 Medan during the 2025/2026 academic year. The research employs the Research and Development (R&D) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects consisted of 26 students from class VII-T1 at SMP Muhammadiyah 01 Medan. The validation results indicate a high validity index with scores of 77.5% from the material expert, 90% from the media expert, and 95% from the language expert, resulting in an average validation score of 85.03%, which falls under the “Highly Valid” category. The teacher’s response to the PowerPoint was 98.07%, while the students’ response was 89%, with an average score of 93.535%, categorized as “Highly Practical.” The effectiveness of the media is demonstrated by a classical learning mastery level of 87.5%, which is categorized as “Highly Effective.” The average N-gain score was 0.64, indicating a moderate category. Therefore, the iSpring-based PowerPoint developed in this study can serve as an innovative and effective alternative learning medium to enhance students’ mathematical problem-solving abilities.